A Rapid, Simple DNA Mismatch Repair Substrate Construction Method - Kinsella, Timothy J.; Du, Weinan (Frontiers in Oncology, 2011)
A more flexible and higher yielding in vitro DNA mismatch repair (MMR) substrate construction method, which was developed initially by Wang and Hays, is described for the construction of a nucleotide-based chemical mismatch (G/IU) and a G/T mismatch. Our modifications use the combination of two endonuclease enzymes (NheI and BciVI) and two new redesigned plasmids (pWDAH1A and pWDSH1B). In our modified methodology, plasmids are initially digested with the nicking endonucleases, followed by the streptavidin treatment. The mismatch-containing oligo is then annealed to the gap DNA and finally ligated to produce a mismatch-containing DNA substrate. We report a high ligation efficiency (up to 90%) of these mismatch substrates and confirm recognition using a functional assay. These modifications, coupled with the use of the redesigned plasmids, can be applied for the construction of other types of chemically induced mismatches as well as insertion-deletion loops (IDL) for future in vitro studies of MMR processing by our group and others.